Cause-related marketing and strategic agility: An integrated framework for gaining the competitive advantage - Christofi, Michael; Kaufmann Hans, Ruediger; Vrontis, Demetris; Leonidou, Erasmia (My University, 2013)
This article posits a framework that illustrates how the concepts of strategic agility and cause-related marketing are synthesised in order to generate a sustainable competitive advantage through superior brand awareness and positive corporate reputation. In addition, this paper reflects how CRM and strategic agility, in the context of creating and sustaining a competitive advantage in a hyper-dynamic environment, can complement and magnify each other's traditional context of analysis. Moreover, this article appears to be the first of its kind to theoretically examine the dynamics implied by synthesising these, so far, distinct concepts. In conclusion, the authors posit a set of research directions designed to enable scholars to further advance the integration of strategic agility and CRM from both problem-driven theory development as well as theory-driven practice management perspectives. Copyright © 2013 Inderscience Enterprises Ltd.
Keywords: CRM; Strategic agility; Brand awareness; Cause-related marketing; Competitive advantage; Corporate reputation